Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Otoriter terhadap Loyalitas Melalui Kepuasan Kerja dan Stres Kerja Karyawan Institusi X di Kediri: The Influence of Organizational Culture and Authoritarian Leadership Style on Loyalty through Job Satisfaction and Job Stress of Employees of Institution X in Kediri - Sari, Herlinda Maya Kumala (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2016)
The purpose of this research to examine the influence of organizational culture and authoritarian leadership style on loyalty through job satisfaction and job stress. Respondents in this study are 82 empolyees of “X” bureau in Kediri. Data is taken from questionnaires which were distributed to the employees randomly. The analysis applied Smart Partial Least Square 2.0 (smarPLS 2.0). The results showed that organizational culture has neither significant positive effect nor the negative on loyalty through job satisfaction. Organizational culture also has no significant negative effect on loyalty through the job stress, while authoritarian leadership style has a significant positive effect on loyalty. Authoritarian leadership style has no significant negative effect on loyalty through job satisfaction, and authoritarian leadership style has no significant negative effect on loyalty through the job stress.